Complex permeability studies of Ni-Co-Zn ferrites synthesized by an oxalate precursor method - Ghodake, J. S.; Kambale, R. C.; Kulkarni, S. D.; Sawant, S. R.; Suryavanshi, S. S. (Smart Materials & Structures, 2009)
Nanocrystalline Co-substituted Ni-Zn ferrites have been synthesized by employing a co-precipitation technique using oxalate precursors. The co-precipitated oxalates were decomposed in air at 650 degrees C for 1 h and the powder was sintered at 1000 degrees C. The phase formation of the sintered ferrite was confirmed by x-ray diffraction studies. The lattice parameter a (angstrom) increases with the addition of Co(2+) which is attributed to the large ionic size of Co(2+) (0.78 angstrom), which replaces Ni(2+) (0.74 angstrom). The crystallite size has been estimated by the Debye-Scherrer formula using the full width at half-maximum (FWHM) of the line broadening of the (311) reflection and it is found to be in the range of 25-28 nm. Also, with increasing cobalt content the magnetocrystalline anisotropy constant (K(1)) and magnetostriction constant (lambda(s)) increase, and the grain size decreases, hence the value of initial permeability mu(i) decreases. The saturation magnetization M(s) and magnetic moment (n(B)) do not show any significant variation for all compositions varying with the cobalt content.

Cobalt nanoparticles doped emaraldine salt of polyaniline: a promising room temperature magnetic semiconductor - Hatamie, Shadie; Kulkarni, M. V.; Kulkarni, S. D.; Ningthoujam, R. S.; Vatsa, R. K.; Kale, Sangeeta N. (Journal of Magnetism and Magnetic Materials, 2010)
Incorporation of magnetic nanoparticles in polymers with organic functional groups working as semiconducting substrate is of immense interest in the field of dilute magnetic semiconductors (DMS) and spintronics. In this article we report on synthesis and evaluation of dilutely doped (0-10 wt%) cobalt nanoparticles in emaraldine salt (ES) of polyaniline in the presence of dodecyl benzene sulfonic acid (DBSA) and p-toluene sulfonic acid (p-TSA) using a sonochemical-assisted-reduction approach as a possible DMS candidate. The X-ray diffraction pattern and high resolution transmission electron microscopy (HRTEM) image show the ES to be polycrystalline, in which 10 nm sized Co nanoparticles get embedded in its FCC structural form. From Fourier transform infrared (FT-IR) and UV-visible (UV-vis) spectroscopy studies, it is predicted that cobalt particles get electrostatically bound to the specific SO(3)(-) ion sites of ES, thereby modifying torsional degrees of freedom of the system. The applied field dependent magnetization study shows that the sample exhibits hysteresis loop with a minimal doping of 3 wt% of Co nanoparticles and increases with the amount of Co nanoparticles in ES due to dipolar interaction. The electron transport data show that with increase in Co wt% there is a gradual shift from ohmic to non-ohmic response to the sample bias, accompanied by opening of electrical hysteresis and an increased resistance. The non-linear response of higher doped systems has been attributed to the combination of direct and Fowler-Nordheim tunneling phenomena in these systems. Persistence of optical and transport properties of the polymer, with an introduction of magnetic moment in the system, envisages the system to be a fine magnetic semiconductor. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Cobalt nanoparticles; Magnetic semiconductor; polyaniline